A Novel Dual-Targeted α-Helical Peptide With Potent Antifungal Activity Against Fluconazole-Resistant Candida albicans Clinical Isolates - Yang, Yang; Wang, Chenxi; Gao, Nan; Lyu, Yinfeng; Zhang, Licong; Zhang, Sujiang; Wang, Jiajun; Shan, Anshan (Frontiers in Microbiology, 2020)
Due to compromised immune system, fungal infection incidences have markedly increased in the last few decades. Pathogenic fungi have developed resistance to the clinically available antifungal agents. Antifungal resistance poses a great challenge to clinical treatment and has stimulated the demand for novel antifungal agents. A promising alternative to the treatment of fungal diseases is the use of antimicrobial peptides (AMPs). However, the antifungal activities of AMPs have not been fully determined. Therefore, this study aimed at designing and screening α-helical peptides with potential antifungal activities. The effects of key physicochemical parameters on antifungal activities were also investigated. A series of lengthened and residue-substituted derivatives of the template peptide KV, a hexapeptide truncated from the α-helical region of porcine myeloid antimicrobial peptide-36, were designed and synthesized. Enhancement of hydrophobicity by introducing aromatic hydrophobic amino acids (tryptophan and phenylalanine) significantly increased the efficacies of the peptides against Candida albicans strains, including fluconazole-resistant isolates. Increased hydrophobicity also elevated the toxic properties of these peptides. RF3 with moderate hydrophobicity exhibited potent anticandidal activities (GM = 6.96 μM) and modest hemolytic activities (HC10 > 64 μM). Additionally, repeated exposure to a subinhibitory concentration of RF3 did not induce resistance development. The antifungal mechanisms of RF3 were due to membrane disruptions and induction of reactive oxygen species production. Such a dual-targeted mechanism was active against drug-resistant fungi. These results show the important role of hydrophobicity and provide new insights into designing and developing antifungal peptides. Meanwhile, the successful design of RF3 highlights the potential utility of AMPs in preventing the spread of drug-resistant fungal infections.